The Promise of Nanopore Technology: Advances in the Discrimination of Protein Sequences and Chemical Modifications. Issue 11 (18th June 2020) - Cressiot, Benjamin; Bacri, Laurent; Pelta, Juan
Abstract: Only a small percent of human genomic DNA encodes for proteins. Additionally, protein isoforms variants and chemical modifications are not coded in the genome read by the cell machinery. The resulting protein diversity is deeply involved in regular and diseased cellular processes. One challenge for the field of biotechnology, after human genome sequencing, will be to decipher the proteome at a single molecule scale to analyze single‐cell protein variability. In fact, cellular proteic information, often used as a source of biomarkers, is of great importance for early disease detection. This review discusses the proteome's complexity from its genetic source to fully modified proteins. It focuses on the principle of nanopore data analysis and how to obtain information from an electrical current trace. Specifically, the most recent developments in detection, sequencing and post‐translational discrimination of amino acids, peptides and proteins, are described. The main results obtained in this field are discussed and the nanopore techniques to other classical or single‐molecule approaches are compared. Abstract : Detection of low copy protein information, i.e., biomarkers, is critical for early disease detection. Focusing on technical advancements, the state of nanopore protein technology is discussed and compared. This article discusses the most recent developments in sequencing and detection of post‐translational modifications at amino acid, peptide, and protein levels.